ASPEK-ASPEK ESTETIKA UKIRAN KAYU KHAS PALEMBANG PADA AL QURAN AL AKBAR - Husni Mubarat; Heri Iswandi (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2018)
The research of Palembang wood carving art on Al Quran Al Akbar is the study toward aesthetic values. This research aims at revealing the aesthetic values and embodiment process of Palembang wood carving art on Al Quran Al Akbar until its presentation. This research used qualitative research method having descriptive characteristics with the approach of aesthetic study. Visually, the aesthetic values of Palembang wood carving art on Al Quran Al Akbar were the carving of Al Quran calligraphy, the blend of gold and reddish brown colours as the unique characteristics of Palembang wood carving, the existence of ornamental variety as the ornamentation of Palembang wood carving. The aesthetic values of Palembang wood carving can also be explored through values contained in that artwork such as religious, cultural and historical values. The aesthetic values of Palembang wood carving on Al Quran Al Akbar are presented through its presentation built in the form of museum so that artwork becomes a monumental artwork namely the icon of religious tourism in Palembang.